PENGARUH UKURAN AUDITOR DAN SPESIALISASI AUDITOR TERHADAP KUALITAS LABA - Herusetya, Antonius (UI Scholars Hub, 2009)
Prior research had documented that The Big 4 auditors have higher audit quality than non-Big 4 auditors (Teoh and Wong 1993), and The Big 4 auditors with industry specialization have higher audit quality than The Big 4 auditors without specialization (Balsam et al. 2003; Knechel et al. 2007; Behn et al. 2008; Romanus et al. 2008). With the sample o f 139 firm years from manufacturing public companies listed in bursa Efek Indonesia in the year 2005 and2006, this study examines whether the public companies audited by The Big 4 auditors has higher earnings quality (measured by earning response coefficient) than the non-Big 4 auditors. This study also examines whether The Big 4 auditors with industry specialization has higher earnings quality than The Big 4 auditors without industry specialization. This study provides no evidence that there is an earnings quality difference between public companies audited by The Big 4 auditors and non-Big 4 auditors, and between auditors with industry specialization and without specialization. The additional tests on public companies audited by non-Big 4 auditors provide no evidence whether there is an association between CAR and unexpected earning (UER). Consistent with the main result, the sensitivity test on specialization measurement also give evidence that The Big 4 auditors are not differ from the non-Big 4 auditors. This study provides some evidence, consistent with prior studies that the market negatively reacts higher on the companies with negative unexpected earnings, and with higher leverage; and positively reacts higher on the high growth companies audited by The Big 4 auditors. This study leaves some ambiguous results regarding the audit quality o f auditors and earning quality o f public companies in the context o f Indonesia, and provides some opportunities fo r further indepth research in these areas.